Identifikasi Pengendalian Mutu Terhadap Efektivitas dalam Mencapai Implementasi 14001 pada PT. Shinto Kogyo Indonesia - Anita Novianti; Gladecia Naomi Angelica H; Nisa Aisyah; Rizka Nur Aulia; Siti Ismayanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to identify the influence of quality control on the effectiveness of ISO 14001 implementation at PT. Shinto Kogyo Indonesia. Using a qualitative method with a descriptive approach and triangulation technique, the study investigates how quality management impacts the company's environmental performance. Research findings demonstrate that leadership involvement, strategic planning, and the application of the PDCA (Plan-Do-Check-Act) cycle play a crucial role in the successful implementation of environmental management systems. The research emphasizes the importance of management commitment, environmental aspect identification, and continuous corrective actions in achieving effective ISO 14001 standards.